Tomographic evaluation of the prevalence of the intraosseous branch of the posterior superior alveolar artery - Eduardo Claudio Lopes de Chaves e Mello Dias; Julia Bellinazzi de Andrade Santos; Khalila Chequer Cotrim; Fabiano Caparo de Brito (Wolters Kluwer Medknow Publications, 2019)
Background: Despite being well documented and relatively safe, sinus lifting procedures can result complications. Aims: This study aimed to evaluate the presence of the intraosseous branch of the posterior superior alveolar artery (ibPSAA) at the surgical access point for maxillary sinus floor elevation procedure. Materials and Methods: A total of 583 tomography slices of 89 patients were analyzed for the presence or absence of this branch. The frequency of the presence of the artery, its diameter, its distance to the maxillary sinus floor, and its distance to the alveolar ridge according to the anatomical region related to the mentioned teeth were also measured. Results: The ibPSAA was visualized using the tomography in 50 patients (56.2%); a total of 583 tomography slices were evaluated and the vessel was identified in 219 slices. The artery had a diameter smaller than 1 mm in 67.9% of the cases and >1 mm in 32.1% of the cases. Conclusion: The present study provides information regarding the anatomy, presence, and most frequent location and size of the ibPSAA and revealed a risk of considerable hemorrhage in 32.1% of the cases, as the ibPSAA had a diameter >1 mm.